Survival in rhino-orbito-cerebral mucormycosis: An international, multicenter ID-IRI study - Cag, Yasemin; Erdem, Hakan; Gunduz, Mehmet; Komur, Suheyla; Ankarali, Handan; Ural, Serap; Rello, Jordi (Elsevier, 2022)
Background: Mucormycosis is an emerging aggressive mold infection. This study aimed to assess the outcome of hospitalized adults with rhino-orbito-cerebral mucormycosis (ROCM). The secondary objective was to identify prognostic factors in this setting. Methods: This study was an international, retrospective, multicenter study. Patients' data were collected from 29 referral centers in 6 countries. All qualified as proven cases according to the EORTC/MSGERC criteria. Results: We included 74 consecutive adult patients hospitalized with ROCM. Rhino-orbito-cerebral type infection was the most common presentation (n = 43; 58.1%) followed by rhino-orbital type (n = 31; 41.9%). Twenty (27%) had acquired nosocomial bacterial infections. A total of 59 (79.7%) patients (16 in combination) received appropriate antifungal treatment with high-doses of liposomal amphotericin B. Fifty-six patients (75.7%) underwent curative surgery. Thirty-five (47.3%) required intensive care unit admission (27; 36.5% under mechanical ventilation). Hospital survival was 56.8%, being reduced to 7.4% in patients with invasive mechanical ventilation. A multivariate binary backward logistic regression model identified confusion at admission (OR 11.48), overlapping hospital-acquired infection (OR 10.27), use of antifungal treatment before diagnosis (OR 10.20), no surgical debridement (OR 5.92), and the absence of prior sinusitis (OR 6.32) were independently associated with increased risk for death. Conclusion: Today, ROCM still has high mortality rate. Improving source control, rational therpy, and preventing nosocomial infections may improve survival in this severe infection.
Keywords: Mucormycosis; Rhino-orbito-cerebral mucormycosis; Risk Factors; Debridement; Neutropenia; Hospital-acquired infection